HBR's 10 must reads : (Harvard Business Review Press, 2011)
Change is the one constant in business, and we must adapt or face obsolescence. Yet certain challenges never go away. That's what makes this book "must read." These are the 10 seminal articles by management's most influential experts, on topics of perennial concern to ambitious managers and leaders hungry for inspiration--and ready to run with big ideas to accelerate their own and their companies' success